Field investigation and parametric study of greenhouse gas emissions from railway plain-line renewals. (January 2016) - Krezo, Steven; Mirza, Olivia; He, Yaping; Makim, Polly; Kaewunruen, Sakdirat
Highlights: Lifecycle carbon emission from plain-line railway renewal activities are firstly presented. Extensive monitoring and measurements of railway construction management practices were conducted. Field data suggests the carbon footprint due to ballasted track construction and maintenance is less than that of ballastless tracks over the lifespan. Significantly more maintenance emission in ballastless track bed can be observed at the 30 and 60 year interval. Emissions from the embodied carbon of railway construction materials are the dominant contributor. Prolonging the reconstruction frequency by optimal routine maintenance activities is the key to reducing lifecycle CO2 -e emissions. Abstract: Railway transportation is becoming increasingly important in many parts of the world for mass transport of passengers and freight. This study was prompted by the industry's need to systemically estimate greenhouse gas emissions from railway construction and maintenance activities. In this paper, the emphasis is placed on plain-line railway maintenance and renewal projects. The objective of this study was to reduce the uncertainties and assumptions of previous studies based on ballasted track maintenance and renewal projects. A field-based data collection was carried out on plain-line ballasted track renewals. The results reveal that the emissions from the materials contribute more than nine times the CO2 -e emissions than the machines used in the renewal projects. The results show that extending the lifespan of rail infrastructure assets through maintenance is beneficial in terms of reducing CO2 -e emissions. Analysis was then carried out using the field data. Then the results were compared to two ballastless track alternatives. The results show that CO2 -e emissions per metre from ballasted track were the least overall, however, the maintenance CO2 -e emissions are greater than those of ballastless tracks over the infrastructure lifespan, with ballasted track maintenance emitting more CO2 -e emissions at the 30 and 60 year intervals and the end of life when compared to the ballastless track types. The outcome of the study can provide decision makers, construction schedulers, environmental planners and project planners with reasonably accurate GHG emission estimates that can be used to plan, forecast and reduce emissions for plain-line renewal projects.